2003
DOI: 10.1002/app.12694
|View full text |Cite
|
Sign up to set email alerts
|

Thermal memory of polyethylenes analyzed by temperature modulated differential scanning calorimetry

Abstract: Temperature modulated differential scanning calorimetry (TMDSC) was employed to study the melting and crystallization behavior of various polyethylenes (PEs). Samples of high density PE (HDPE), low density PE (LDPE), linear low density PE (LLDPE), and very low density PE (VLDPE) with different crystal structures and morphologies were prepared by various thermal treatments (isothermal crystallization and slow, fast, and dynamic cooling). The reversing and nonreversing contributions, measured on the experimental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 39 publications
(81 reference statements)
1
10
0
Order By: Relevance
“…Several melting events for neat HDPE and the graphene nanocomposites were observed, since the melting peaks were broad and overlapping. Multiple endotherm phenomena for HDPE under various crystallization conditions have been observed in the literature [43][44][45]. In particular, G. Amarasinghe et al [44] reported that the process of melting, recrystallization, and remelting occurs in HDPE sample; A. Toda et al [25] reported that the crystals formed at low temperatures are unstable and easily re-organize during heating.…”
Section: Melting Behavior Following the Non-isothermal Crystallizatiomentioning
confidence: 99%
“…Several melting events for neat HDPE and the graphene nanocomposites were observed, since the melting peaks were broad and overlapping. Multiple endotherm phenomena for HDPE under various crystallization conditions have been observed in the literature [43][44][45]. In particular, G. Amarasinghe et al [44] reported that the process of melting, recrystallization, and remelting occurs in HDPE sample; A. Toda et al [25] reported that the crystals formed at low temperatures are unstable and easily re-organize during heating.…”
Section: Melting Behavior Following the Non-isothermal Crystallizatiomentioning
confidence: 99%
“…In method-1, the test specimens were punched from the GMB sheets as cylinders and were placed in DSC pans without encapsulation as shown in Figure 4a. The formation of double peaks in the first melting curve could be due to: (a) not encapsulating the specimen, or (b) the different physical characteristic of the specimens (i.e., specimen thicknesses perpendicular to pan base and the contact area between the specimen and the pans, Figure 4) that were different for specimens taken from 0.5, 1.0, 1.5, 2.0 and 2.4 mm GMBs, which affected the heat transfer from the specimens to the pans and, in turn, affected the recording of heat flow by DSC sensors (Hill et al 1999;Gabbott 2007), or (c) a different population of lamellae thicknesses (Wunderlich and Czornyj 1977;Wtochowicz and Eder 1984;Cebe and Chung 1990;Amarasinghe et al 2003) in the GMBs having different melting points resulting from different thermal and stress histories experienced by the GMBs of different thickness during processing (despite being made from the same resin and during the same production run as discussed earlier). The latter explanation is supported by several lines of evidence.…”
Section: Enthalpies Of Melting and Crystallisationmentioning
confidence: 99%
“…It is still necessary to further develop the understanding of the conduction mechanisms linked with the physical and chemical structure of the polymer. Numerous studies have dealt with the effects of additives and temperature in relation to the electrical properties and morphology of polyethylene [1,2]. The additives have a direct influence on the crystallinity rate, the spherulite diameter, the density and the nature of the traps [3].…”
Section: Introductionmentioning
confidence: 99%
“…The additives have a direct influence on the crystallinity rate, the spherulite diameter, the density and the nature of the traps [3]. Polyethylene morphology, and particularly the percent crystallinity, is mostly dependent on cooling rate from the melt, as well as time and temperature of annealing [2]. In this paper PEA and TSDC experimental measurements are compared to the numeric simulations obtained from a bipolar model developed for polyethylene [4] with the objective of a better understanding of the effect of trapped space charge on classical TSDC measurements.…”
Section: Introductionmentioning
confidence: 99%